Threats to the Global Economy in the Context of the COVID Pandemic on the Example of Russia and China (Global Journal of Management and Business Research, 2023)
In a crisis different economic systems react differently to the emergence of imbalances If the state regulation of economic processes is minimized in the market economic system then in the command and administrative system the state has many tools for regulating the economy The purpose of the study is to empirically demonstrate the co-directional and opposite dynamics of the development of modern economic systems in order to assess the conjuncture of socio-economic development in the conditions of the COVID pandemic
Keywords: economic system; market economy; command and administrative economy; russia; china